Early Verb Morphological Development of a Bangla-speaking Child. Issue 3 (3rd July 2021) - Sultana, Asifa
ABSTRACT: Crosslinguistic research into language development reveals that typological features determine children's developmental patterns to a large extent. The present study examines the early morphological development in the verb inflectional paradigm in Bangla. Data from the first 6 months since the emergence of two-word combinations were collected from a monolingual Bangla-speaking child. Emergence of individual inflectional markers and their error patterns were identified, and interpreted with references to a range of proposals and crosslinguistic findings. The results are of significance for building a developmental profile of typically-developing Bangla-speaking children as we all for measuring the levels of development in atypically-developing children.